The new! abs diet for women : the 6-week plan to flatten your belly and firm up your body for life - Zinczenko, David (Rodale, 2010)
Explains how women can lose pounds quickly and dramatically reshape their bodies, while maintaining the principles of a safe, healthy, and nutritionally balanced diet, covering such topics as preventing osteoporosis and managing menopausal symptoms.